Integration scenarios of virtual worlds in learning management systems using the MULTIS approach - Morgado, Leonel (2017)
This work further clarifies how the MULTIS architecture can be used for integration of virtual worlds in learning management system (LMS) for organizational management of e-learning activities, as an extension to a previous work published in the proceedings of VEAI 2016. Current LMSs provide minimal support for educational use in an organizational context, and other integration efforts assume that educators are inside the virtual world, accessing the LMS as an external service. Our approach enables educators to set up and manage virtual world activities from within the traditional LMS Web interface as an integral part of the overall educational activities of a course. The MULTIS architecture foresees several alternative communication channels between LMS and virtual worlds, including the spooling of automated clients or “bots” and the flexibility to inject code if necessary and possible. In this work, we detail the application of this architecture and its approach in several sample scenarios, based on previous analysis of integration requirements. It is the result of a joint effort by academic and corporate teams, implemented and tested in the Formare LMS for OpenSimulator and Second Life Grid virtual world platforms.